Comedies of nihilism : the representation of tragedy onscreen - Khan, Amir (Palgrave Macmillan, 2020)
This book presents close-readings of seven post-millennial comedic films: Up in the Air, Tropic Thunder, JCVD, Winnebago Man, The Trotsky, Be Kind Rewind, and Hamlet 2. It is a sequel to Stanley Cavell’s 1981 landmark study of the comedic genre, Pursuits of Happiness, where he examines seven comedies of Hollywood’s “Golden Age.” Khan puts forward the idea that comedies, once centred on the conventional “happy ending,” are no longer interested in detailing the steps to any ending we might call happy. Instead, the agenda of most culturally serious comedies today is to “spoof,” to make all that is fair foul. The seven films presented here risk a type of cultural nihilism―spoofing for the sake of spoofing and nothing else, indicative not of film’s promise but its failure.By equating the failure of film with the failed national politics of Canada (or the failed politics of nationalism and community more generally), this study shows that comedy has less to do with happiness and more to do with the grotesque. The films analysed represent hyper-realized forms of comic irony and move towards what theatre knows as tragedy, or a tragic vision